Elasticity of Nacrite: Implications for Subduction Zone Dynamics - Das, Ishita; Shukla, Gaurav (Geochemistry, geophysics, geosystems : G3, 2024)
Subduction zones exhibit heterogeneities in composition due to different mineral assemblages transported into the mantle by the descending slabs, thus affecting the seismic properties of the region. These minerals are typically rich in alumina and silica and often contain hydrous phases. Nacrite, Al2Si2O5(OH)4, a mineral consisting of these components, forms in basaltic crust through hydrothermal alteration and is frequently overlooked due to its structural alikeness with its polytypes, making it hard to distinguish by traditional methods. Its occurrence in oceanic sediments and altered basaltic crust significantly impacts the subduction process by facilitating the transport of water into deeper mantle regions. In this study, we investigate the equation of state and elasticity of nacrite using first‐principles calculations based on density functional theory corrected for dispersive forces over its pressure stability range. Anomalous behavior of elastic coefficients are suggestive of a polytypic transformation, evidenced by anomalous softening in the shear modulus and a decrease of approximately 3% in shear wave velocity observed at low pressures (∼ ${\sim} $ 2 GPa). Our studies indicate that nacrite exhibits a significantly lower shear wave velocity compared to the surrounding mantle, resulting in very high VP/VS ratios. These findings emphasize the role of nacrite in the subduction zones of Japan and Alaska, particularly in the formation of low‐velocity layers. We propose that nacrite's presence is a significant factor explaining these observations, alongside other hydrous minerals like lawsonite, glaucophane, etc., contributing to the low‐velocity layers in these regions. Plain Language Summary Subduction zones are highly varied because they contain a range of minerals with different chemical compositions and physical properties. Many minerals from the Earth's crust get recycled back into the mantle in these zones, creating diverse characteristics. The presence of water‐containing (hydrous) minerals can sometimes trigger large earthquakes or contribute to the formation of molten rock at various depths. Crustal minerals tend to be rich in aluminum and silica thus stabilizing hydrous minerals in their lithology. One such mineral, nacrite, contains about ∼26% ${\sim} 26%$ water (as hydroxyl, or OH) and forms when basaltic crust undergoes hydrothermal alteration. Nacrite present in low‐velocity mineral assemblages may lead to the formation of low‐velocity layers in Japan and Alaskan subduction settings. Our findings further suggest that nacrite may undergo a structural transformation like its kaolin family members: kaolinite and dickite. This transformation is accompanied by a decrease in shear wave velocity. These findings enhance our understanding of the intricate connection between depth‐dependent velocity anomalies in the subduction process and the role of water‐binding minerals such as nacrite. Key Points Nacrite exhibits pressure‐induced structural transformations under low pressures, leading to a notable decrease in shear modulus and shear wave velocity The low shear wave velocities and notably high VP/VS ratios resemble low‐velocity layers of subducting slabs in Japan and Alaska Exhibiting exceptionally high shear wave velocity anisotropy, nacrite stands unparalleled among hydrous minerals found in subducting slabs